Development of a biosensor telemetry system for monitoring fermentation in craft breweries. (1st March 2017) - Farina, Donatella; Zinellu, Manuel; Fanari, Mauro; Porcu, Maria Cristina; Scognamillo, Sergio; Puggioni, Giulia Maria Grazia; Rocchitta, Gaia; Serra, Pier Andrea; Pretti, Luca
Highlights: Integration of glucose and ethanol biosensors in a miniature telemetry device. Use of the telemetry device for monitoring top and bottom fermentations in wort samples. Biosensor data resulted in good agreement with reference methods. Abstract: The development and applications of biosensors in the food industry has had a rapid grown due to their sensitivity, specificity and simplicity of use with respect to classical analytical methods. In this study, glucose and ethanol amperometric biosensors integrated with a wireless telemetry system were developed and used for the monitoring of top and bottom fermentations in beer wort samples. The collected data were in good agreement with those obtained by reference methods. The simplicity of construction, the low cost and the short time of analysis, combined with easy interpretation of the results, suggest that these devices could be a valuable alternative to conventional methods for monitoring fermentation processes in the food industry.